Couplets : Travels in Speculative Pragmatism - Massumi, Brian (Book collections on Project MUSE., 2021)
"This collection of twenty-four essential essays written by Brian Massumi over the past thirty years is both a primer for those new to his work and a supplemental resource for those already engaged with his thought."--